An analysis of the book selection practices of Filipino parents - Calijan, Krystelle Joy A. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Selecting quality books for children to read does not necessarily follow a distinct standard. For a book to be the best for a child, it must reflect his own experiences and must share the same values and beliefs with him. Therefore, the role of parents in selecting books for their children is indispensable because they are the primary caregivers of the children, which makes them the most knowledgeable of their backgrounds and personalities.